A CROSS-NATIONAL STUDY TO TEST THE SHARED RESOURCE HYPOTHESIS IN DEPRESSION CONCORDANCE WITHIN OLDER ADULT COUPLES. (16th November 2018) - Lu, P; Shelley, M
Abstract: Health concordance has been commonly found within couples in many countries. The shared resources hypothesis suggests that married couples share the same environmental resources, which therefore shapes their health concordance. Yet so far, no studies have tested the cross-cultural applicability of this hypothesis. Cross-sectional 2012–2013 Health Retirement Survey family data from China, England, Mexico, and the United States were analyzed. Shared resources within couples were measured by the number of living children and income earners, amount of household income, attaining higher education, pensions, and health insurance. Mental health was measured by the Center for Epidemiologic Studies Depression Scale. A multiple-group structural equation model estimated by full information maximum likelihood and bootstrapping was used to test the hypothesis across genders. Results indicated none of the coefficients was significant in the model for China. For Mexican couples, higher education was associated with increased spousal depression concordance. Being more highly educated, working for pay, and having more sources of pensions and health insurance were associated with increased depression concordance within American and British couples. Good self-rated health was the most consistent and robust predictor of higher depression concordance across all countries except China. Results were similar across gender for all countries. The shared resources hypothesis explained depression concordance within older adult couples in the U.S. and England. Having more financial resources or higher socioeconomic status was associated with increased depression concordance within American and British couples. However, strong evidence of the applicability of the hypothesis was not found in China and Mexico.